Allergy after a sandwich: case report of beer allergy in an adolescent - Nico, João F.; Mendes, Vera; Maia, Estefânia; Rubino, Gina; Lemos, Sónia (International Journal of Contemporary Pediatrics, 2026)
Beer is an uncommon cause of IgE-mediated food allergy despite its widespread consumption. We report an adolescent who developed generalised urticaria and lip angioedema immediately after eating a traditional Portuguese sandwich with a beer-based sauce. He had previously experienced two episodes of delayed generalised urticaria after ingesting small amounts of beer. Serum specific IgE was positive for barley (7.12 kU/l) and barley malt (21.7 kU/l). Prick-to-prick testing was positive for four commercially available beers containing barley malt. He tolerated other barley-containing foods, suggesting that malting and brewing may modify barley proteins and/or generate clinically relevant allergens. The patient was counselled to avoid beer, whisky and foods prepared with barley-malt alcoholic beverages, and was prescribed an adrenaline auto-injector due to the potential risk of anaphylaxis. This case underscores that beer allergy, although rare in paediatrics, should be considered in adolescents presenting with acute urticaria or angioedema after beer consumption or exposure through cooking.